Pengembangan Metode Penstrukturan Masalah Berbasis Cognitive Map dan Strategic Choice Approach dan Penerapannya pada Masalah Manajemen Rantai Pasokan - Iwan Mumin Basarah; Sani Susanto (Institute of Research and Community Outreach - Petra Christian University, 2016)
The problem structuring methods used to deal with complex and ill-structured problems. One of the method of structuring ill-structured problem is the Strategic Choice Approach (SCA), while one of the problems of complex and ill-structuredproblems is a supply chain management problems. This research proposes the use of a cognitive map as a base application of SCA on the problems of supply chain management at PT X, a leading manufacturing company in Indonesia. Three main results of this study are structuring problems, choosing of the top priority problems, and choosing of troubleshooting options among other identified options.